(untitled) (INNOVATIVE ECONOMY, 2025)
Huk Yu.V. DIAGNOSTICS OF INSTITUTIONAL SMOOTHING OF SPATIAL POLARIZATION OF TOURISM SERVICE PROVISION Purpose. The aim of the article is to analyse the processes and institutional mechanisms that contribute to the reduction of asymmetries and imbalances in the development of tourism activities between different regions, which will allow identifying directions and forming mechanisms for smoothing the spatial polarization of the provision of tourism services in the form of certain recommendations. Methodology of research. The following primary methods were used to achieve the goal in the article, (for collecting information about the facts of overtourism) and secondary methods (for systematizing the received data) were used. According to the method of implementation, logical-analytical and visual methods were used, namely, deduction and induction methods for identifying factors contributing to the formation of excessive tourism and identifying measures that allow it to be smoothed out, scientific analysis for using statistical information on international tourism activities and visualization of information on overtourism, UNESCO World Heritage Sites, etc. in the form of tables. Findings. It was studied that global destinations of OECD countries that were affected by overtourism are duplicated in the UNESCO World Heritage List. This poses a dilemma for them: to further develop the destination, risking losing the status of a world monument, or to limit the influx of visitors, risking losing income. In contrast, in emerging markets, the majority of those interested in transforming UNESCO World Heritage Sites into global tourist destinations and at the state and municipal levels welcome the increase in tourism entrepreneurship. It was established that the state of overloading of global tourist destinations with tourists has different effects on the degree of public resistance. Thus, in destinations located in resort areas, the most protest is against the appearance and behaviour of tourists, in museum destinations against excessive crowding in central areas. Protests against rising housing prices occur in socially oriented countries, whose governments have the authority to intervene in the market economy in order to improve the situation of the poorer segments of the population. It was substantiated that the concentration of tourists in a destination leads to overpopulation, increased pressure on local resources and degradation of the natural environment and cultural heritage. At the same time, the concentration of tourist activity can vary significantly in different regions and destinations around the world, which significantly complicates their systematization. We have grouped destinations according to the similarity of their social and economic mechanisms of operation, highlighting the following types: iconic and popular destinations, large cities, coastal and beach areas, places of exceptional natural beauty, UNESCO World Heritage sites. It was proven that a high ratio of tourists to city residents not only creates discomfort for everyone, but also causes disappointment among tourists themselves, and creates the impression of the destination as overvalued. In our opinion, it is advisable to smooth out spatial polarization by increasing the offer in territories not involved in the tourism process, which have an interesting history. Thus, the creation of large industrial centres of recreational and memorial zones based on the revitalization of industrial heritage provides a tool for asymmetric smoothing of spatial polarization. It was established that online travel agencies (OTAs), booking platforms and travel aggregators have gained popularity, providing travellers with convenient access to a wide range of services. As of the end of 2023, Expedia, Booking.com and Airbnb have become significant players in the travel and tourism industry. Thus, online platforms have increased price transparency in the tourism market. Expedia, Booking.com and Airbnb have a planetary reach, which makes it easier for small or remote destinations to attract more visitors. This has led to the activation of economic activity in less attractive tourist destinations and contributed to the development of the economy of regions that are little known to international tourists and the redirection of tourist flows, which reduces the anthropogenic load on global tourist destinations. At the same time, OTAs create problems for traditional travel agencies and small hotel chains. It was substantiated that the concentration of economic activity and resources in certain territories leads to a difference in income levels. High-paying jobs, investment opportunities and business development are usually concentrated in economically vibrant regions, while other regions receive lower wages and overcome unemployment. Such a difference in income can have various social and economic consequences, including blocking social elevators, public discontent and lack of basic services for the poorer segments of the population. Thus, stakeholders of the tourism business of a particular region must increase their own development potential by seeking access to capital, developing their own modern infrastructure. At the same time, the low level of education and technology in these areas can hinder their ability to attract investment, develop the tourism sector and create sustainable economic growth. Originality. For the first time, the motivational theory of expectations of V. Vroom was applied to the motivation of a person to go on a tourist trip, namely, that the physiological presence of the body’s need for recreation makes a person think about what needs to be done to relax. However, the decision where, how and when this will happen is made by a person under the influence of expectations, hopes and valence from staying in the chosen destination, which, provided that tourist destinations use appropriate software, allows avoiding overtourism, or at least weakening its manifestation. The grouping of destinations according to the similarity of their social and economic mechanisms of functioning was improved, highlighting the following types: iconic and popular destinations, large cities, coastal and beach areas, places with exceptional natural beauty, UNESCO World Heritage sites, which allows for more clearly tracking recreational areas with an increased concentration of economic activity. Practical value. In general, the diagnosis of the system of institutional smoothing of spatial polarization of the provision of tourist services can become the basis for developing recommendations for its improvement, which will contribute to a more balanced and sustainable development of tourist regions. Key words: international tourism, tourist services, spatial polarization of tourist activity, stakeholders, revitalization of industrial heritage, UNESCO World Heritage, overtourism, recreational resources, tourist destination.